Implementasi Metode Pembelajaran Demontrasi Melalui Media Audio Visual untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Fiqih di MTs Muhammadiyah-13 Tanjung Morawa - Salsabila Matondang; Juli Maini Sitepu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to explain the learning methods used by teachers in order to increase students' learning motivation and explain the application of demonstration learning methods using audio-visual media to increase students' learning motivation at MTs Muhammadiyah 13 Tanjung Morawa. This research uses qualitative research methods with a descriptive approach. Fiqh is one of the Islamic religious education subjects that provides encouragement to students to be able to apply it in everyday life. By using the demonstration method and in the learning process it can provide a clear picture that can be seen by students, with the teacher practicing and providing verbal explanations about the material being taught. The results of the writing show that through the results of the observations that the author has made, the teachers have carried out the taharah procedures using the demonstration method. After the demonstration method is implemented in taharah material in fiqh subjects, it provides concrete understanding to students.